Transformasi Air Terjun Sempor sebagai Destinasi Wisata Alternatif Berbasis Masyarakat - Devi Al Choiriyah; Muhamad; Putri Rima Oktaviyandari; Sandi Rahmat Alzari (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2026)
The emergence of new rural tourism destinations often originates from informal local practices rather than formal planning processes. Sempor Waterfall is one example of a natural tourism destination that has emerged in Dusun Turi, Sleman, Special Region of Yogyakarta, Indonesia, and has undergone transformation. Initially, the area was utilized by local youth for river tracing activities, informal recreation, and resource collection, and it later developed into a recognized tourism attraction. This study aims to analyze the transformation process and development dynamics of Sempor Waterfall as an alternative tourism destination. A qualitative descriptive approach was employed, with data collected through field observations, in-depth interviews with community members and stakeholders, and documentation. The analysis reveals that the development process was driven by a bottom-up approach involving local youth groups and supported by a university community service program (KKN-PPM UGM). The findings highlight that everyday practices played a significant role in shaping the early formation of the destination, while limited resources encouraged adaptive and collaborative strategies. Furthermore, the study identifies that the transformation phase is crucial in determining the direction of future tourism development, particularly in terms of sustainability and community involvement. In conclusion, the case of Sempor Waterfall demonstrates that community-led, low-capital initiatives can effectively transform local natural resources into alternative tourism destinations, contributing to the broader discourse on community-based and emerging rural tourism.